THE ROLE OF PAI LEARNING IN SHAPING STUDENTS' RELIGIOUS CHARACTER IN THE DIGITAL AGE: INTEGRATION OF ARTIFICIAL INTELLIGENCE-BASED MEDIA - Juariah, Siti; Yahya, Muhamad Slamet (Jurnal Konseling Pendidikan Islam, 2026)
In the digital age marked by advances in information technology, PAI learning plays an important role in shaping students' religious character. This study aims to explore how the integration of artificial intelligence (AI)-based media can improve the effectiveness of PAI learning and support the development of students' religious character. The methods used in this study are literature review and qualitative analysis of various relevant sources. The results of the study indicate that the application of AI can enhance students' engagement in cognitive, affective, and behavioral aspects, which positively impacts the cultivation of religious character. However, the use of AI must be supported by a strong Islamic value and ethical framework, content monitoring, and teacher involvement as moral role models. With an integrative and targeted learning model, the combination of PAI and AI-based media can be an effective strategy to address the challenges of the digital age and strengthen students' religious identity sustainably.